Effect of Density and Number of Layers of Fiber Sheets and End Anchors on the Flexural Capacity of SRG-Strengthened RC Beams - Andrea Incerti; Valentina Rinaldini; Mattia Santandrea; Christian Carloni; Claudio Mazzotti (Buildings)
Steel-reinforced grout (SRG) composites are a newly developed retrofitting technique, which is considered an alternative to other fiber-reinforced composites to increase the load-carrying capacity of existing structures. This work presents an experimental campaign aimed at investigating the response of reinforced concrete (RC) beams strengthened with SRG externally applied to the tension side of the member to improve flexural capacity. The number of fiber sheet layers and fiber sheet density have been varied to evaluate the effectiveness of the retrofitting system. For some beams, different solutions of anchors at the ends of the beams have been considered to delay the premature debonding of the SRG. Moreover, single-lap direct shear tests have been carried out on concrete prisms strengthened with the same SRG composite to evaluate the bond behavior of the system. Failure modes, load responses, and corresponding flexural capacity (beam tests) and debonding loads (shear tests) are reported. The moment–curvature curves derived from cross-sectional analysis are compared with the corresponding experimental curves. The strain when the loss of composite action occurs is obtained from the curvature measured experimentally and compared with the values from formulas for the strain available in the literature and the strain at debonding in single-lap shear tests.